Analysis of Revenue Recognition Based on PSAK No. 23 at PT PLN (Persero) UIP3B Sulawesi - Ratu Winda, Gusrianti; Azis, Muhammad; Masnawaty (Muhasabatuna : Jurnal Akuntansi Syariah, 2024)
The purpose of this research was to find out whether the method applied by PT. PLN (Persero) UIP3B Sulawesi in recognizing and measuring its income is in accordance with the Statement of Financial Accounting Standards (PSAK) No. 23. The method used in this research is a qualitative descriptive method using primary data obtained from interview techniques and direct observation with company finance staff, as well as using secondary data from income recording documents and financial reports of PT PLN (Persero) UIP3B Sulawesi. The results of this research indicate that PT PLN (Persero) UIP3B Sulawesi recognizes revenue based on the Accrual Basis concept . Where revenue is recognized when services have been provided even though cash has not been received or is in accordance with Statement of Financial Accounting Standards (PSAK) No. 23 and income is measured using fair value.